The Synergistic Use of IL-15 and IL-21 for the Generation of NK Cells From CD3/CD19-Depleted Grafts Improves Their ex vivo Expansion and Cytotoxic Potential Against Neuroblastoma: Perspective for Optimized Immunotherapy Post Haploidentical Stem Cell Transplantation - Heinze, Annekathrin; Grebe, Beatrice; Bremm, Melanie; Huenecke, Sabine; Munir, Tasleem Ah.; Graafen, Lea; Frueh, Jochen T.; Merker, Michael; Rettinger, Eva; Soerensen, Jan; Klingebiel, Thomas; Bader, Peter; et al. (Frontiers in Immunology, 2019)
Neuroblastoma (NB) is the most common solid extracranial tumor in childhood. Despite therapeutic progress, prognosis in high-risk NB is poor and innovative therapies are urgently needed. Therefore, we addressed the potential cytotoxic capacity of interleukin (IL)-activated natural killer (NK) cells compared to cytokine-induced killer (CIK) cells for the treatment of NB. NK cells were isolated from peripheral blood mononuclear cells (PBMCs) by indirect CD56-enrichment or CD3/CD19-depletion and expanded with different cytokine combinations, such as IL-2, IL-15, and/or IL-21 under feeder-cell free conditions. CIK cells were generated from PBMCs by ex vivo stimulation with interferon-γ, IL-2, OKT-3 and IL-15. Comparative analysis of expansion rate, purity, phenotype and cytotoxicity was performed. CD56-enriched NK cells showed a median expansion rate of 4.3-fold with up to 99% NK cell content. The cell product after CD3/CD19-depletion consisted of a median 43.5% NK cells that expanded significantly faster reaching also 99% of NK cell purity. After 10-12 days of expansion, both NK cell preparations showed a significantly higher median cytotoxic capacity against NB cells relative to CIK cells. Remarkably, these NK cells were also capable of efficiently killing NB spheroidal 3D culture in long-term cytotoxicity assays. Further optimization using a novel NK cell culture medium and a prolonged culturing procedure after CD3/CD19-depletion for up to 15 days enhanced the expansion rate up to 24.4-fold by maintaining the cytotoxic potential. Addition of an IL-21 boost prior to harvesting significantly increased the cytotoxicity. The final cell product consisted for the major part of CD16-, NCR-expressing, poly-functional NK cells with regard to cytokine production, CD107a degranulation and antitumor capacity. In summary, our study revealed that NK cells have a significantly higher cytotoxic potential to combat NB than CIK cell products, especially following the synergistic use of IL-15 and IL-21 for NK cell activation. Therefore, the use of IL-15+IL-21 expanded NK cells generated from CD3/CD19-depleted apheresis products seems to be highly promising as an immunotherapy in combination with haploidentical stem cell transplantation for high-risk NB patients.